PREPARING SOCIAL WORKERS FOR ALTERNATIVE DISPUTE RESOLUTION IN CARE AND PROTECTION CASES - Matthias, Carmel (Social Work/Maatskaplike Werk, 2014)
The Children’s Act 38 of 2005 contains provisions enabling utilisation of alternative dispute resolution (ADR) in cases involving children. This article focuses on the specialised training required to prepare social workers to be effective ADR practitioners. By drawing on comparative data, the article demonstrates that it is essential for social workers to receive such training in South Africa. The nature of the training that would be required to empower South African social workers to be effective ADR facilitators in care and protection cases is explored. Proposals for a South African training programme are put forward.